(untitled) (Olhar de Professor, 2019)
The article investigated the meanings attributed by children to their experiences at playground. The theoretical framework adopted is based on some interlocutors of Socioanthropology of Childhood, among other authors who are also part of Childhood Studies and had play and children’s cultures as sources of study. The research was characterized as qualitative and the methodology included participant observation and interviews through Drawings with Stories that allowed us to know how they relate to their peers and adults and also contributed to look the school playgroung from their perspective, as well as think your education. In this sense, the research on the playground proved relevant by presenting the importance of listening to children in the organization of daily work aiming to overcome the adult perspective so present in institutional routines. KEYWORDS: Childhood; Playground; Pre School.